2000
DOI: 10.2134/agronj2000.925974x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Yield Distribution of Cool‐Season Grasses following Winter Defoliation

Abstract: monly referred to as the summer slump. This poor seasonal growth distribution is a common challenge faced Graziers in southeastern USA often stockpile forage in late summer by graziers, forcing them to buy feed or rely on stored to extend the grazing season and reduce feeding costs. The effect of forages. If spring yields are distributed over a larger winter grazing on the following growing seasons production in the window of time, graziers may be able to manage the upper Midwest has not been reported. This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 23 publications
3
25
0
Order By: Relevance
“…In the upper Midwest, Riesterer et al (2000) also found little eff ect of time of winter harvest on subsequent yield except when early spring growth preceded March defoliation, reducing fi rst-cut forage yield. In the upper Midwest, Riesterer et al (2000) also found little eff ect of time of winter harvest on subsequent yield except when early spring growth preceded March defoliation, reducing fi rst-cut forage yield.…”
Section: Month Stagedmentioning
confidence: 93%
“…In the upper Midwest, Riesterer et al (2000) also found little eff ect of time of winter harvest on subsequent yield except when early spring growth preceded March defoliation, reducing fi rst-cut forage yield. In the upper Midwest, Riesterer et al (2000) also found little eff ect of time of winter harvest on subsequent yield except when early spring growth preceded March defoliation, reducing fi rst-cut forage yield.…”
Section: Month Stagedmentioning
confidence: 93%
“…Furthermore, B. inermis is a common grass in pastures and grasslands where it often co‐occurs with S. phoenix (e.g. Riesterer et al . 2000).…”
Section: Methodsmentioning
confidence: 99%
“…Care must be taken to ensure that both whole-plot factors are randomized independently and differently in each replicate of the experiment, rather than stripping one factor across the entire experiment without rerandomization. Combined use of both strip-plot and traditional split-plot "splits" in one experiment (Riesterer et al, 2000) illustrate both the complexity and versatility available in these randomization restrictions.…”
Section: Blockingmentioning
confidence: 99%